Women and Beauty in Nordin Hassan's Plays (Malay Literature, 2013)
Sasterawan Negara Dato (Dr.) Noordin Hassan has often been accused of being "women-struck" by critics who do not understand the meaning of beauty other than the physical aspect. The objective e of this paper is to clarify this misconception using the Islamic framework of analysis of the meanings of "women" and "beauty". Noordin understands the need for balance in the life of mankind and the meaning of Divine Feminine to be an attribute of God. Women are neither chattels nor objects of admiration to be displayed by men, rather to be partners in life, mothers of future generations. Through his plays, Noordin has raised the level of women characters as leaders to demonstrate that the capability of mankind is not determined by gender but by the knowledge within. Raised by his mother, surrounded by other women in his growing years, it is no wonder that Noordin finds women of better quality than men, but only women of hasanah.Keywords: women, beauty, divine feminine, Islamic